Indonesia Words Detection Using Fingerprint Winnowing Algorithm - Sunardi Sunardi; Anton Yudhana; Iif Alfiatul Mukaromah (Jurnal Informatika, 2019)
The action of plagiarism is bad deeds that violate the code of ethics in the world of writing that often occur in the academic environment, the lack of interest in reading and creativity of the nation is one of the factors that cause obstruction of the progress of a nation. Besides the plagiarism action bad for good name at a college which is caused by the plagiarist. This needs to be minimized or prevented so that the problem does not happen again. the use of fingerprint in winnowing algorithm can solve the problem. winnowing algorithm is an algorithm used to match a word for word with hashing method, the use of n-gram and w-gram is very influential on result of similarity.